Benefits and harms of lung cancer screening in HIV-infected individuals with CD4+ cell count at least 500 cells/μl. (19th June 2018) - Kong, Chung Yin; Sigel, Keith; Criss, Steven D.; Sheehan, Deirdre F.; Triplette, Matthew; Silverberg, Michael J.; Henschke, Claudia I.; Justice, Amy; Braithwaite, R. Scott; Wisnivesky, Juan; Crothers, Kristina
Abstract : Objective: Lung cancer is the leading cause of non-AIDS-defining cancer deaths among HIV-infected individuals. Although lung cancer screening with low-dose computed tomography (LDCT) is endorsed by multiple national organizations, whether HIV-infected individuals would have similar benefit as uninfected individuals from lung cancer screening is unknown. Our objective was to determine the benefits and harms of lung cancer screening among HIV-infected individuals. Design: We modified an existing simulation model, the Lung Cancer Policy Model, for HIV-infected patients. Data sources: Veterans Aging Cohort Study, Kaiser Permanente Northern California HIV Cohort, and medical literature. Target population: : HIV-infected current and former smokers. Time horizon: : Lifetime. Perspective: : Population. Intervention: Annual LDCT screening from ages 45, 50, or 55 until ages 72 or 77 years. Main outcome measures: Benefits assessed included lung cancer mortality reduction and life-years gained; harms assessed included numbers of LDCT examinations, false-positive results, and overdiagnosed cases. Results of base-case analysis: For HIV-infected patients with CD4 + cell count at least 500 cells/μl and 100% antiretroviral therapy adherence, screening using the Centers for Medicare & Medicaid Services criteria (age 55–77, 30 pack-years of smoking, current smoker or quit within 15 years of screening) would reduce lung cancer mortality by 18.9%, similar to the mortality reduction of uninfected individuals. Alternative screening strategies utilizing lower screening age and/or pack-years criteria increase mortality reduction, but require more LDCT examinations. Limitations: Strategies assumed 100% screening adherence. Conclusion: Lung cancer screening reduces mortality in HIV-infected patients with CD4 + cell count at least 500 cells/μl, with a number of efficient strategies for eligibility, including the current Centers for Medicare & Medicaid Services criteria. Abstract : Supplemental Digital Content is available in the text